2017
DOI: 10.1111/nyas.13512
|View full text |Cite
|
Sign up to set email alerts
|

Lambert–Eaton myasthenic syndrome: mouse passive‐transfer model illuminates disease pathology and facilitates testing therapeutic leads

Abstract: Lambert-Eaton myasthenic syndrome (LEMS) is an autoimmune disorder caused by antibodies directed against the voltage-gated calcium channels that provide the calcium ion flux that triggers acetylcholine release at the neuromuscular junction. To study the pathophysiology of LEMS and test candidate therapeutic strategies, a passive-transfer animal model has been developed in mice, which can be created by daily intraperitoneal injections of LEMS patient serum or IgG into mice for 2-4 weeks. Results from studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
0
7
0
3
Order By: Relevance
“…In Drosophila melanogaster , voltage-gated shaker (K v ) channels were shown to be up-regulated following knockout of BK channels, such that block of K v channels with 4-aminopyridine caused a large increase in transmitter release at the NMJ ( Lee et al, 2008 ; see, however, Warbington et al, 1996 ). This treatment is thought to increase Ca 2+ entry and vesicle release because the block of K v channels widens the presynaptic action potential ( Wang et al, 2016 ; Meriney et al, 2018 ; Ng et al, 2017 ). We tested the effect of the K v channel blocker 3,4-DAP in WT and BK −/− NMJs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila melanogaster , voltage-gated shaker (K v ) channels were shown to be up-regulated following knockout of BK channels, such that block of K v channels with 4-aminopyridine caused a large increase in transmitter release at the NMJ ( Lee et al, 2008 ; see, however, Warbington et al, 1996 ). This treatment is thought to increase Ca 2+ entry and vesicle release because the block of K v channels widens the presynaptic action potential ( Wang et al, 2016 ; Meriney et al, 2018 ; Ng et al, 2017 ). We tested the effect of the K v channel blocker 3,4-DAP in WT and BK −/− NMJs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cells in SCLC have a neuroendocrine origin and express the same types of VGCCs as nerve terminals, therefore the immune system develops antibodies against these cancer proteins and misdirects against the nervous system. 4 A preclinical study emphasized the potential of ICIs to enhance and misdirect spontaneously occurring antitumor immune responses against the nervous system, thus causing PNSs. 5 Furthermore, some case reports showed that LEMS developed as a potential neurological irAE in patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…This then impairs ACh vesicle release through a variety of mechanisms that affect the active zone of a neuromuscular junction: downregulation of presynaptic P/Q-type VGCCs, disorganization of vesicle release sites, and upregulation of alternative calcium channels. 2,3 Variable release of ACh results in failure of neuromuscular transmission, manifesting as weakness, autonomic dysfunction, or both. LEMS can occur as a paraneoplastic syndrome associated with malignancy (cancer-associated LEMS) or as an autoimmune phenomenon in the absence of malignancy (nontumor LEMS).…”
Section: Pathophysiologymentioning
confidence: 99%
“…LEMS is a presynaptic disorder characterized by the dysfunctional release of ACh vesicles at the neuromuscular junction due to the presence of antibodies to the pore-forming α1A subunit of the P/Q-type VGCC. This then impairs ACh vesicle release through a variety of mechanisms that affect the active zone of a neuromuscular junction: downregulation of presynaptic P/Q-type VGCCs, disorganization of vesicle release sites, and upregulation of alternative calcium channels 2,3 . Variable release of ACh results in failure of neuromuscular transmission, manifesting as weakness, autonomic dysfunction, or both.…”
Section: Lambert-eaton Myasthenic Syndromementioning
confidence: 99%